Liver dysfunction in children with hematologic malignancy or solid tumor - Rita Carmelia; Bidasari Lubis; Adi Sutjipto; Trie Hariweni (Indonesian Pediatric Society, 2003)
Background Deficiencies in liver synthetic function can only bedetected if the damage is severe, which are more often due to nonhepatic factors such as malignancies, both hematologic and solidtumor.Objective To assess liver function in children with either hemato-logic malignancy or solid tumor and to find out which one of themmostly affects liver function.Methods A retrospective study was conducted on 125 childrenwith malignancies in the Sub division of Hemato-Oncology De-partment of Child Health, Adam Malik Hospital, Medan, from Janu-ary 1999 until May 2000. The inclusion criteria included all pa-tients who were younger than 15 years and had not received anytreatment yet. The differences between prevalent liver dysfunctionin both groups were assessed by using chi-square test; Fisher’sexact test was used to know the type of liver cell damage.Results Liver dysfunction occurred in both types of malignancies. Adecrease of albumin level was not significant in both groups. Therewas a statistically significant difference between the prolongedprothrombine time (PT) in hematologic malignancy (26.4%) and thatin solid tumor (10.4%) with p=0.03. There was no significant differ-ence in the elevation of serum transaminase concentration, totalbilirubin, and alkaline phosphatase. Based on aspartate aminotrans-ferase (AST) and alanine aminotransferase (ALT) ratio, we foundthat the type of liver cell damages was infiltrative disorders, occurred13 out of 20 cases with elevated AST and ALT.Conclusion Liver dysfunction occurred in both types of malig-nancy; it occurred more frequently in hematologic malignancy thanin solid tumors